Optimalisasi Sterilisasi Eksplan Daun Kopi Arabika Sidikalang (Coffea arabica L.) Untuk Penanaman In Vitro - Lubis, Theresia; Harahap, Fauziyah; Damanik, Jesika Febriani; Batubara, Wardah Arijah; Adelia, Ichlasul; Apriliani, Dwi; Sohada, Ummi (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to determine the effect and identify the optimal sterilization pattern for suppressing contaminant growth in the in vitro culture of Sidikalang Arabica coffee (Coffea arabica L.) leaf explants. The experiment was conducted using a completely randomized design (CRD) with five treatment levels and 15 replications. Data were analyzed using the Kruskal Wallis test, and if significant differences were found, the Mann Whitney test was applied at a 5% significance level. The results showed that sterilization patterns significantly affected the time to contamination onset, the percentage of contaminated explants, the percentage of browning explants, and the percentage of explants forming callus. However, no significant effect was observed on the time of callus initiation. Sterilization pattern 5 was identified as the most optimal in suppressing contamination, with the lowest contamination percentage (6,6%), browning (6,6%), and the highest callus formation (93,3%). This pattern involved washing with detergent; soaking in Agrept (30 minutes) and Benlate (30 minutes); followed by sterilization in a laminar airflow cabinet (LAFC) using Tween 20 (20 minutes), graded Bayclin at 10%, 20%, and 30% (for 20, 15, and 5 minutes, respectively), 70% alcohol (20 seconds), and ascorbic acid (20 minutes).